Tunable tactile aynapses wnabled by erasable doping in iongel-gated nanotube network transistors - Huang, Yan; Zhou, Yaoqiang; Wieland, Sonja; Li, Yachen; Zhao, Ni; Zaumseil, Jana (Advanced functional materials, 2025)
The tunable synaptic plasticity of biological sensory systems plays a pivotal role in efficient information processing and adaptation. Bio-mimetic sensory synaptic devices, particularly those for tactile synapses, usually lack effective sensory gating control and thus exhibit limited adaptability to external stimuli. Here, an artificial tactile synaptic sensor is introduced that mimics the features of biological systems. The monolithic device utilizes an iongel-gated single-walled carbon nanotube (SWCNT) network transistor with slow but reversible electrochemical doping characteristics. Utilizing an iongel with a mechanosensitive 3D structure, the device demonstrates pressure sensing ability and nonvolatile changes to the p-doping of the SWCNT network that depend on pressure amplitude and duration and enable long-term memory of pressure signals for up to ≈22 h. The device can work in excitatory or inhibitory mode. In both cases, the synaptic plasticity can be adjusted independently from the tactile stimulus by varying the gate voltage, which emulates the intrinsic plasticity of biological systems. Furthermore, the time-dependent and spatially nonuniform doping of the SWCNT channel during and after pressure loading is corroborated through in situ photoluminescence imaging. This visualization of the doping process in SWCNT networks provides direct insights into the operation mechanism underlying the nonvolatile pressure response in these artificial tactile synaptic sensors.
Online verfügbar: 05. März 2025
Gesehen am 19.08.2025